Предмет: Математика,
автор: Logan228grifer
Решите пж понятно
3 1/5:(z-1/2)=2 2/3:(z+1/3)
Ответы
Автор ответа:
2
2 2/3 * ( z - 1/2 ) = 3 1/5 * ( z + 1/3)
8/3 *( z - 1/2 ) = 16/5 * ( z + 1/3)
8/3z - 8/6 = 16/5z + 16/15
8/3z - 16/5z = 16/15 + 8/6
40/15z - 48/15z = 16/15 + 20/15
-8/15z = 36/15
z = -36/15 * 15/8
z = -4,5
8/3 *( z - 1/2 ) = 16/5 * ( z + 1/3)
8/3z - 8/6 = 16/5z + 16/15
8/3z - 16/5z = 16/15 + 8/6
40/15z - 48/15z = 16/15 + 20/15
-8/15z = 36/15
z = -36/15 * 15/8
z = -4,5
Logan228grifer:
спс
8/3 *( z - 1/2 ) = 16/5 * ( z + 1/3)
8/3z - 8/6 = 16/5z + 16/15
8/3z - 16/5z = 16/15 - 8/6
40/15z - 48/15z = 16/15 + 20/15
-8/15z = 36/15
z = -36/15 * 15/8
z = -4,5
Похожие вопросы
Предмет: Литература,
автор: byryndyk3825
Предмет: Українська мова,
автор: Frhdytu9959
Предмет: Математика,
автор: Areyou7326
Предмет: Математика,
автор: 87051942714